Wireless IoT smart door lock using Viola-Jones face detection technique / Samsiah Ahmad...[et al.] - Samsiah, Ahmad; Muhammad Farhan, Ramli; Zalikha, Zulkifli; Lily Marlia, Abdul Latif (UiTM Press, 2020)
Technology in Industrial revolution 4.0 has rapidly changed with the advancement technology developments, including the technology of Internet of Things (IoT). With IoT, different types of data either structured or unstructured can be collected and transferred over the Internet that attracted researchers to conduct various empirical studies on automation of home security environment mainly with intelligence system. This project highlights a face detection of smart door lock system based on Viola-Jones technique. The fundamental system design, implementation of hardware and software as well as the data collection and processing techniques are described in this paper. The prototype of the wireless IoT Smart Door Lock based on Viola-Jones face detection technique has been tested and the accuracy of classification at different face angles (front, left, right, top, down) were recorded and also presented in this paper. The results show that Viola-Jones algorithm has achieved 88% of average accuracy on the complete faces classification.